The Martha's Vineyard beach and book club : a novel [large type] - Kelly, Martha Hall (Random House Large Print Publishing, 2025)
"Two sisters living on Martha's Vineyard during World War II find hope in the power of storytelling when they start a wartime book club for women-a spectacular novel inspired by true events from the New York Times bestselling author of Lilac Girls"-- Provided by publisher.